DATA PROTECTION OFFICER: REGULATORY FRAMEWORK UNDER THE EU GENERAL DATA PROTECTION REGULATION - Zaleskis, Julius (Teisė, 2017)
The new EU General Data Protection Regulation sets forth a body of rules on data protection officer, which should be at the centre of the new legal framework, however, provides for uncertainty regarding content thereof. The article reveals new developments of the regulation on data protection officers, the content of grounds for appointment of the data protection officer, defines principles upon which activities of the data protection officer should be based.